Report on correlation of zooplankton with physico- chemical factors from freshwater temple pond. - K, Tidame S; S, Shinde S (Journal of Experimental Sciences, 2013)
In the present work, we provide quantitative information on the correlation of zooplankton with physico-chemical factors from man-made reservoir in the Nashik district. In the study period we have recorded 16 genera of zooplankton, of which 10 genera belong to rotifera, 3 genera belong to cladocera and 3 genera belong to copepoda. Among zooplankton, particularly rotifera was the dominant group throughout the study period and highest count was recorded in the monsoon season, cladocerans noted least throughout the year. The results indicate that the distribution and density of zooplankton species influenced by physical and chemical factors of the environment.